1991
DOI: 10.1111/j.1439-037x.1991.tb00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sulphydryl Compounds in Improving Dry Matter Partitioning and Grain Production of Maize (Zea mays L.)

Abstract: Three sulphydryl compounds, viz., 2-mercaptoethanol, 2-mercaptoethylamine and thiourea, were tested for improving dry matter partitioning and grain production of maize in field culture. The chemicals were applied ca. 0.1 % concentration as foliar spray at grain formation stage. Mercaptoethanol, mercaptoethylamine and thiourea increased grain yield ha"' by 18.1, 29.2 and 34.1 %, respectively compared with water control Significant improvement in harvest index, a measure of dry matter partitioning for grain prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…Thiourea has also been reported to significantly improve growth, yield and water use efficiency of mungbean, Yadav (2005). Thiourea induced increase in seed yield due to better translocation of photosynthates has also been reported earlier Sahu and Solanki (1991), Parihar et al (1998), Sharma et al (2015). Anjum et al (2008) and Bhunia et al (2015).…”
Section: Growth Attributesmentioning
confidence: 58%
“…Thiourea has also been reported to significantly improve growth, yield and water use efficiency of mungbean, Yadav (2005). Thiourea induced increase in seed yield due to better translocation of photosynthates has also been reported earlier Sahu and Solanki (1991), Parihar et al (1998), Sharma et al (2015). Anjum et al (2008) and Bhunia et al (2015).…”
Section: Growth Attributesmentioning
confidence: 58%
“…Combined application of thiourea and phosphorus also significantly improved plant growth and seed yield of clusterbean under water stress (Burman et al 2004). It has been suggested that effects of thiourea are due to its sulphydryl group rather than the amino group as thiourea spray was found significantly better than spray with urea in maize crop (Sahu and Solanki 1991). Application of thiourea significantly increased leaf area at the flowering stage (50 DAS) and the favourable effects were more pronounced when applied as seed treatment plus foliar spray ( Figure 2).…”
Section: Crop Growth and Yieldmentioning
confidence: 95%
“…Thiourea, a sulph-hydryl compound (NH 2 -CS-NH 2 ) is known for breaking dormancy and stimulating germination. However, it may have more diverse biological activities of SH group and is known to improve photosynthetic efficiency (Hernandez-Nital et al 1983;Sahu and Solanki 1991). Improvement in plant growth and development due to application of thiourea has also been observed in crops like maize (Sahu et al 1993), wheat (Sahu and Singh 1995) and pearl millet (Parhiar et al 1998).…”
Section: Introductionmentioning
confidence: 97%
“…responsible for biological fixation of N to increase the efficiency of pulses as soil renovator and serves the dual purpose of increasing yield of main as well as succeeding crop. An adequate supply of phosphorus has been reported well for better growth, yield, quality and enormous nodule formation in legumes (Sammauria et al, 2009) (Jocelyn, 1972 Use of thiourea, recognized as plant growth regulator (Sahu and Solanki, 1991) may be helpful in this regard. The exogenous supply of growth regulators also modifies plant growth by hormonal control, differentiation, morphogenesis and key physiological processes such as carbon and nutrient assimilation, partitioning of photosynthates and utilization efficiency.…”
Section: Issn: 2319-7706 Volume 6 Number 10 (2017) Pp 2841-2847mentioning
confidence: 99%
“…Significant improvement in the seed yield due to foliar spray of 500 ppm thiourea was also reported by Burman et al, (2008) and Bamaniya (2009) in mungbean. While explaining the role of sulphydryl compounds in maize productivity, Sahu and Solanki (1991) were of the view that probably photosynthates transport was improved because of improved dry matter partitioning. The partitioning of dry matter in plants depends on its distribution between leaves, stem and sink.…”
Section: Effect Of Thioureamentioning
confidence: 99%